Tantangan Pengembangan Kapasitas e-Government di Provinsi Aceh - Eli Jumaeli (Puslatbang KHAN, 2013)
E-Government Development in Aceh aims to improve the quality of the administration of the Government of Aceh-based communications and information technology in order to provide information services to the public in a transparent and accountable through the web. In the management of information and documentation (PID) is still experiencing problems in terms of vagueness management division of tasks between the scope of the Bureau of Public Relations Dishubkomintel Setdaprov, lack of understanding of PID among officials, employees who have a limited ability to manage the PID. This paper recommends the importance of capacity development of e-Government of Aceh in three dimensions, namely the dimension of the system needs to be Governor Regulation on the management of PID; institutional dimension, need to strengthen coordination between the PID management organization, and dissemination of e-government officials and staff, and planning officials PID functional.